Multi-objective power generation expansion planning with high penetration of renewables. (January 2018) - Luz, Thiago; Moura, Pedro; de Almeida, Aníbal
Abstract: This paper presents a multi-objective model for expansion with a high share of renewable energy. The model considers three objective functions (minimizing the total cost, maximizing generation at the peak load, and maximizing the contribution of non-hydro renewable sources). The model was then applied to the Brazilian case, using the new government targets for renewable energy. The introduction of the objectives regarding peak load and non-hydro renewable generation lead to an increase of solar power generation. In many studies about Brazil, solar power was not considered, or its participation was negligible, but in this paper the results show solar energy as the main non-hydro renewable source in 2030, due to its capacity to meet the peak demand, since its daily curve coincides with the peak load period. In this study, it was possible to meet 90% of the annual load with renewable sources (with 23% being ensured by non-hydro) and the solar power increased from 21 MW to 40000 MW by 2030.